A pesquisa teórica em psicanálise: das suas condições e possibilidades - Tavares, Leandro Anselmo Todesqui [UNESP]; Hashimoto, Francisco [UNESP] (My University, 2013)
This article is part of the methodological approach concerning theoretical investigation aspects, developed from the analysis of research in Psychoanalysis. Due to its peculiarities, research in Psychoanalysis raises issues and questions which advance far beyond the positivist conceptions which underline the dominant paradigm of our present day production of knowledge. Considering Psychoanalysis as the effect of the psychoanalitic act in itself, mainly when considering its theoretical scientific approach which must be part of a specific method, the following question is raised: what are the real possibilities of research in Psychoanalysis, specifically theoretic al research in Psychoanalysis? The article aims at articulating relevant issues concerning the field of Psychoanalysis and their relevant development for research in this field. To sum up, the article highlights issues concerning the role of the researcher as a necessary and decisive condition for any theoretical research in the field of Psychoanalysis.

O presente artigo representa parte metodológica de um percurso de investigação teórica, desenvolvida a partir de reflexões sobre um trabalho de pesquisa em Psicanálise. A pesquisa em Psicanálise, dada suas particularidades, suscita questionamentos e dúvidas de outra ordem que extrapolam por si mesma as concepções de ciência positivista, em suma, os modos dominantes de produção de saber na atualidade. Sendo a Psicanálise efeito, propriamente dito, do ato psicanalítico, inclusive ao considerarmos o seu próprio avanço teórico-científico que deve constituir-se a partir de seu método particular, questionamos: quais as possibilidades de uma pesquisa em Psicanálise, em especial, as pesquisas teóricas em Psicanálise? O artigo propõe-se a articular discussões relevantes inerentes ao campo da Psicanálise e seu desenvolvimento atrelado à pesquisa. Por fim, considera de modo privilegiado uma discussão acerca da implicação do pesquisador, condição necessária e característica de qualquer pesquisa teórica em Psicanálise
Theoretical research in psychoanalysis: conditions and possibilities
Keywords: Psychoanalysis; Psychoanalytic research; Implications; Psicanálise; Pesquisa psicanalítica; Implicações